Mechanisms and Inhibitors of Histone Arginine Methylation. Issue 12 (19th September 2018) - Fulton, Melody D.; Brown, Tyler; Zheng, Y. George
Abstract: Histone methylation plays an important regulatory role in chromatin restructuring and RNA transcription. Arginine methylation that is enzymatically catalyzed by the family of protein arginine methyltransferases (PRMTs) can either activate or repress gene expression depending on cellular contexts. Given the strong correlation of PRMTs with pathophysiology, great interest is seen in understanding molecular mechanisms of PRMTs in diseases and in developing potent PRMT inhibitors. Herein, we reviewed key research advances in the study of biochemical mechanisms of PRMT catalysis and their relevance to cell biology. We highlighted how a random binary, ordered ternary kinetic model for PRMT1 catalysis reconciles the literature reports and endorses a distributive mechanism that the enzyme active site utilizes for multiple turnovers of arginine methylation. We discussed the impacts of histone arginine methylation and its biochemical interplays with other key epigenetic marks. Challenges in developing small‐molecule PRMT inhibitors were also discussed. Abstract : Histone arginine methylation is a high‐profile epigenetic mark, and the enzymes that catalyze arginine methylation, protein arginine methyltransferases (PRMTs), have become attractive drug targets for different diseases including cancer. We discuss the different kinetic mechanisms, histone crosstalk, and progress with inhibitor development.